The Effect Of Time Budget Pressure, Audit Tenure and Public Accounting Firm (Kap) Size On Quality Audit In Banking Companies Listed On The Indonesia Stock Exchange (Idx) In 2019-2021 - Wenny Ana Adnanti; Indarti, Iin; Retno Ginanjar (Jurnal Bingkai Ekonomi (JBE), 2024)
This study aimed to determine the effect of audit tenure, public accounting firm (kap) size and time budget pressure on audit quality. The population of this study were 48 banking companies listed on the indonesia stock exchange (idx) for the 2019-2021 period. The research sample was obtained as many as 14 companies, selected using purposive sampling method with the criteria according to the audit in the financial statements there is a material error of banking companies for 3 consecutive years, from 2019 to 2021 . The analysis technique used logistic regression analysis. The results showed that audit tenure and kap size had no effect on audit quality, and time budget pressure had a effect on audit quality.